Sistem Ekonomi Islam Sebagai Solusi Problematika Sistem Kapitalisme Dan Sistem Sosialisme - M. Indra Gunawan (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
In this study, the title published by the author is the Islamic economic system as a solution to the problems of the capitalism system and the socialism system. This research has a broad scope both in terms of theory and application, for that purpose the objective is to find out the problems of the economic system of Capitalism and the economic system of socialism in overcoming economic problems and to see what is offered by the Islamic economic system in overcoming the problems of the economic system of capitalism and the economic system. economics of socialism, the research methodology used is library research or "Library Research". Because literature review is part of a qualitative research because the form of data presented tends to be more subjective in nature and more to book or literature analysis. From the methodology that the author uses, it is the capitalism system where everyone recognizes private property rights over the means of production. Meanwhile, the economic system of socialism does not recognize private rights and gives ownership rights only to the general public